Vestibular Evoked Myogenic Potential on Ocular, Cervical, and Soleus Muscles to Assess the Extent of Neurological Impairment in HTLV-1 Infection - Silva, Tatiana Rocha; Rocha Santos, Marco Aurélio; Macedo de Resende, Luciana; Labanca, Ludimila; Caporali, Júlia Fonseca de Morais; Scoralick Dias, Rafael Teixeira; Utsch Gonçalves, Denise (Frontiers in Neurology, 2020)
Introduction: Vestibular Evoked Myogenic Potential (VEMP) can be used to test central vestibular pathways from the midbrain to the lumbar spine, according to the muscle tested. Purpose: to compare the spinal cord alteration in individuals with HTLV-1-associated myelopathy (HAM) and with HTLV-1-asymptomatic infection using the VEMP recorded from different muscles. Methods: VEMP was recorded in 90 individuals of whom 30 had HAM, 30 were HTLV-1 asymptomatic carriers, and 30 negative controls. VEMP was recorded in the oculomotor muscle (oVEMP), testing the vestibulo-ocular reflex, and in the cervical muscle (cVEMP) and soleus muscle (sVEMP), testing the vestibulospinal reflex, respectively, in the cervical and in the lumbar spinal level. The type of stimulation was auditory for oVEMP and cVEMP, and galvanic for sVEMP. The compared variables were the latencies of the electrophysiological waves. Results: HTLV-1-asymptomatic group was similar to the controls regarding oVEMP (p=0.461), but different regarding cVEMP (p<0.001) and sVEMP (p<0.001). HAM group has presented the worst latencies and was different from the HTLV-1-asymptomatic group in the VEMP of all the tested muscles (p<0.001). The concomitant occurrence of VEMP alterations in the three recorded muscles of the same individual was found in 2(6.7%) asymptomatic carriers and in 20(66.7%) patients with HAM(p=0.001). The analysis of VEMP alteration per group and per muscle has showed that, in HTLV-1-asymptomatic group, oVEMP was altered in 3(10.0%) individuals, cVEMP in 10(33.3%) and sVEMP in 13(43.3%). In HAM group, oVEMP was altered in 23(76.6%) individuals, cVEMP in 27(90%) and sVEMP in 30(100%). Conclusion: HTLV-1-neurological damage has followed an ascendant progression beginning at the lumbar spine in the stage of a clinically asymptomatic infection, whereas HAM has affected not only the spine, but also the midbrain.